The abundance, diversity and distribution pattern of avian species in the Fentie Community Conservation Area, Ethiopia - Lamesginew Tadesse; Abebayehu Desalegn (Journal of Science and Inclusive Development, 2020)
This study aimed to investigate the species abundance, diversity, and distribution pattern of avifauna in the Fentie Community Conservation Area, East Gojjam, surrounded by farmlands, settlements and mountain ranges. The study carried out in both dry and wet seasons. The study area was stratified based on the four habitat types: forest, woodland, farmland, and shrubland. The point count method was employed in the forest and woodland habitats, and the line-transect used for farmland and shrubland. Data were analyzed using SPSS version 20. In this study, 92 avian species belonging to 38 families were identified during both dry and wet seasons. The highest avian diversity was observed in the forest habitat (H= 4.101 and H= 4.056), followed by shrubland (H=3.874 and H= 3.848), during both dry and wet seasons, respectively. The highest number of birds was recorded in the dry season (n=703) than the wet season (n=439). There was a significant difference in abundance between the habitat types in the dry season (α=0.05, H’=4.142, df=3 and P=0.038) as well as in the wet season (α=0.05, H’=4.113, df=3 and P=0.109). The fewer bird species diversity and abundance discovered in the farmland could be caused by the cleansing of the vegetation for cultivation as it was seen in the study area. Thus, protection of the area is crucial for wildlife conservation especially for birds to enrich their diversity, abundance, and to maintain the natural ecological balance.